UNDERSTANDING INTERNAL LOCUS OF CONTROL: A BIBLIOMETRIC STUDY - Maulidya Alfi Anita Zain,; Sopiah, (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2022)
Those who have an internal locus of control feel that their success depends on their efforts, with an internal locus of control being able to prevent conflicts between family and work demands and reduce a person's stress level. This study aims to dig deeper into the internal locus of control. To achieve this goal, the researcher uses a bibliometric study that takes journals from science direct and uses VOSviewer to perform data analysis. There are 25 articles analyzed from 2020-2022. The results of this study describe 3 aspects, co-authorship, co-accuracy, and citation. The results of this study are expected to be a reference for further research, especially those that raise the title related to an internal locus of control